The progression of deoxynivalenol-induced growth suppression in nursery pigs and the potential of an algae-modified montmorillonite clay to mitigate these effects - Frobose, Hyatt L.; Erceg, Jake A.; Fowler, S. Q.; Tokach, Michael D.; DeRouchey, Joel M.; Woodworth, Jason C.; Dritz, Steven S.; Goodband, Robert D. (My University, 2017)
Two experiments were conducted to characterize the progression of deoxynivalenol (DON)-induced growth suppression and to investigate algae-modified montmorillonite clay (AMMC) as a means to alleviate the effects of DON in nursery pigs. In both experiments, naturally DON-contaminated wheat was used to produce diets with desired DON levels. In Exp. 1, 280 barrows and gilts (10.0 +/- 0.2 kg BW) were used in a 28-d experiment arranged in a 2 x 2 + 1 factorial design with 8 replicates per treatment. The 5 treatments consisted of 2 positive control (PC) diets with DON below detection limits and with or without 0 or 0.50% AMMC and 3 negative control (NC) diets with 5 mg/kg of DON and containing 0, 0.25, or 0.50% AMMC. No DON x AMMC interactions were observed. Overall, pigs fed DON had decreased (P < 0.001) ADG and final BW regardless of AMMC addition. Feeding DON-contaminated diets elicited the most severe depression (P < 0.001) in ADFI and G:F from d 0 to 3, remaining poorer overall (P < 0.01) but lessening in severity as exposure time increased. Pigs fed DON diets had greater (P < 0.05) within pen BW variation (CV) on d 28. Although the addition of 0.50% AMMC to diets restored (P < 0.05) ADFI from d 14 to 21 to levels similar to the PC, no other differences were observed for AMMC inclusion. In Exp. 2, 360 barrows (11.4 +/- 0.2 kg BW) were used in a 21-d experiment with 9 dietary treatments arranged in a 3 x 3 factorial design with DON and AMMC inclusion as main effects. There were 8 replicate pens per treatment. Treatments consisted of 3 PC diets without DON, 3 low-DON (1.5 mg/kg DON) NC diets, and 3 high-DON (3 mg/kg DON) NC diets with 0, 0.17, or 0.50% AMMC incorporated at each DON level. No DON x AMMC interactions were observed. As DON level increased, ADG and final BW decreased (quadratic, P < 0.05), driven by decreased (quadratic, P < 0.01) ADFI and poorer (quadratic; P < 0.05) G:F. At both 1.5 and 3 mg/kg DON, reductions in ADG were most marked from d 0 to 7 (15 to 22% lower) and were least distinct from d 14 to 21 (5 to 6% lower). Incorporating AMMC at increasing levels had no effect on ADG, ADFI, G:F, or final BW. Overall, these experiments reinforce DON effects on feed intake but also indicate that the effects of DON on G: F may be more severe than previously thought. Furthermore, some pigs appear to develop tolerance to DON, as effects on ADFI and G: F lessen over time. However, the addition of AMMC did not offset the deleterious effects of DON.
Citation: Frobose, H. L., Erceg, J. A., Fowler, S. Q., Tokach, M. D., DeRouchey, J. M., Woodworth, J. C., . . . Goodband, R. D. (2016). The progression of deoxynivalenol-induced growth suppression in nursery pigs and the potential of an algae-modified montmorillonite clay to mitigate these effects. Journal of Animal Science, 94(9), 3746-3759. doi:10.2527/jas2016-0663
Keywords: Deoxynivalenol; Detoxifying Agents; Montmorillonite Clay; Nursery Pig; Swine; Vomitoxin